Rancang Bangun Alat Pemberi Pakan Hewan Peliharaan Otomatis Dengan Mikrokontroler Node MCU ESP8266 Berbasis Internet of Things (IoT) Menggunakan Telegram Bot - Putri Ayu Rengganis Suganda; Ari Mulyoto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Pet welfare is a human right that belongs to the animal itself. However, this does not get enough attention from the public or pet owners. Judging from the owner's lack of knowledge of the pets they own and the lack of facilities that support the welfare of the pets themselves. For example, feeding pets that are not on time. Eating is an important process for the body, by eating the body will get the nutrients as well as the energy needed to sustain life. Not only humans. Animals also really need nutrition from their food, especially pets. Based on these problems, more efficient facilities are needed to overcome them, such as animal feeders that can run automatically with the NodeMCU ESP8266 microcontroller which is connected via the Telegram application on a smartphone and food dispensing is operated via a servo motor to open and close the food storage area.